2002
DOI: 10.1016/s1010-7940(02)00247-6
|View full text |Cite
|
Sign up to set email alerts
|

Total anomalous pulmonary venous connection: long-term appraisal with evolving technical solutions

Abstract: Side-to-side anastomosis provides excellent results for TAPVC repair while left atrial enlargement procedures appear to be associated with higher risk of late arrhythmias. Although early and aggressive reintervention for recurrent PV obstruction is mandatory, intrinsic PV stenosis remains a predictor of adverse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
77
2
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 15 publications
6
77
2
11
Order By: Relevance
“…The surgical mortality of TAPVC patients decreased from 80% in early series to 5% in recent reports [5,6]. In our series, the surgical mortality decreased from 45.5% before 2000 to 21.7% after 2000.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…The surgical mortality of TAPVC patients decreased from 80% in early series to 5% in recent reports [5,6]. In our series, the surgical mortality decreased from 45.5% before 2000 to 21.7% after 2000.…”
Section: Discussioncontrasting
confidence: 43%
“…But previous associated studies showed no consistent results [7]. The impact of connection type remains controversial [5][6][7][8].…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have shown that patients with preoperative PVO had lower intubation rates, a higher number of postoperative pulmonary hypertensive crises and episodes, and a greater amount of positive inotropic support during their ICU stays. [18] Sagat et al [15] compared PVO and non-PVO isolated TAPVR patients and found that the PVO patients had longer ICU stays with a higher incidence of ICU complications. However, they reported no significant differences with regard to the duration of surgery and mortality among their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bu obstrüksiyon sıklıkla pulmoner venlerin çaplarının yeterli genişlikte olmamasından kaynaklanmaktadır. Cerrahi sonrası ilerleyici ve devam eden pulmoner hipertansiyon, erken dönemde intrensek venöz obstriksiyonun devam etmesi ile açıklanmaktadır [21][22][23][24]. Bizim serimizde bir hasta pulmoner hipertansif krize bağlı olarak kaybedildi.…”
Section: Discussionunclassified